2014
DOI: 10.1002/pts.2078
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antimicrobial – Containing EVOH Coatings on PP and PET Films: Functional and Active Property Characterization

Abstract: 11Natural antimicrobials are currently being tested by many researchers for active packaging 12 applications as a response to consumer demands for safer food products. In previous works, Results showed that the application of corona discharge followed by a PEI-based primer was the 24 best anchorage treatment available to stabilize EVOH coatings on PP and PET substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…[81] Cerisuelo et al (2014) coated EVOH29 nanocomposites containing 2 wt% bentonite on PP and PET, but found that this did not significantly improve the barrier properties as opposed to the PP and PET samples coated with regular EVOH29. [82] Sadeghi and Shahedi (2016) developed an EVOH/ chitosan polymer mixture film containing nano-ZnO. The incorporation led to a decrease in both P O 2 and P H 2 O when the ZnO content was increased by filling pores in the film matrix and the creation of a tortuous path.…”
Section: Additivesmentioning
confidence: 99%
“…[81] Cerisuelo et al (2014) coated EVOH29 nanocomposites containing 2 wt% bentonite on PP and PET, but found that this did not significantly improve the barrier properties as opposed to the PP and PET samples coated with regular EVOH29. [82] Sadeghi and Shahedi (2016) developed an EVOH/ chitosan polymer mixture film containing nano-ZnO. The incorporation led to a decrease in both P O 2 and P H 2 O when the ZnO content was increased by filling pores in the film matrix and the creation of a tortuous path.…”
Section: Additivesmentioning
confidence: 99%
“…The low concentration of O 2 has no impact on mycotoxin formation in raw materials, while high levels of CO 2 do not guarantee elimination of spoilage. According to other studies, the use of EVOH film possesses protective properties against water vapor and gas permeability [29][30][31]. The asparaguses respiration changes during the first 2 days of storage, which were determined as a crucial factor affecting raw material shelf-life.…”
Section: Discussionmentioning
confidence: 99%
“…Film thickness was measured with a C112-B Mitutoyo micrometer with a precision of 1 µm. Oxygen permeability at 90% RH was determined with an Oxtran 2/21 ML (Mocon, Minneapolis) with the procedure reported elsewhere (Cerisuelo, Gavara, & Hernandez-Munoz, 2014), using a 20 mm 2 test area.…”
Section: Film Preparationmentioning
confidence: 99%